Design of PRS enabled monopole slotted-antenna sensor for breast tumor detection - Tiruganesh Lanka; Divya Chaturvedi; M. V. L. Bhavani; Arvind Kumar (Scientific Reports)
Abstract This article introduces a near-field microwave sensor based on a monopole antenna for breast tumor detection. The designed antenna operates at 2 GHz and is miniaturized by 37% through the etching of two pairs of rectangular slots along its edges, achieving a compact footprint of 0.28λg × 0.42λg (where λg is the guided wavelength at 2 GHz). To enhance gain, a partially reflective surface (PRS) is positioned behind the radiating monopole, increasing the antenna gain from 2.15 to 7 dBi. The monopole antenna is fabricated using Rogers RT5880 (0.787 mm thickness), while the PRS is made from Rogers TMM13i (3.8 mm thickness). The proposed antenna exhibits high radiation efficiency (95–99%) across the 1.9–2.1 GHz bandwidth. A 3D artificial female breast equivalent phantom is developed to evaluate the sensor’s performance. The PRS-enabled antenna is analyzed in terms of reflected and transmitted power variations at different distances from the phantom. Simulation and experimental results confirm that integrating PRS improves the sensor’s sensitivity and its ability to differentiate between healthy and malignant tissues. Furthermore, specific absorption rate (SAR) analysis indicates that an input power of 50 mW meets SAR safety standards. The proposed antenna is compact, simple, and a safer alternative to X-rays, providing a portable solution for effective breast tumor detection.